Chloroplast and Nuclear Genetic Diversity Explain the Limited Distribution of Endangered and Endemic Thuja sutchuenensis in China - Yao, Zhi; Wang, Xinyu; Wang, Kailai; Yu, Wenhao; Deng, Purong; Dong, Jinyi; Li, Yonghua; Cui, Kaifeng; Liu, Yongbo (Frontiers in Genetics, 2021)
Narrow-ranged species face challenges from natural disasters and human activities, and to address why species distributes only in a limited region is of great significance. Here we investigated the genetic diversity, gene flow, and genetic differentiation in six wild and three cultivated populations of Thuja sutchuenensis, a species survived only in the Daba mountain chain, using chloroplast simple sequence repeats (cpSSR) and nuclear restriction site-associated DNA sequencing (nRAD-seq). Wild T. sutchuenensis populations were from a common ancestral population at 203 ka, indicating they reached at the Daba mountain chain before the start of population contraction at the Last Interglacial (LIG, ~120-140 ka). T. sutchuenensis populations showed relatively high chloroplast but low nuclear genetic diversity. The genetic differentiation of nRAD-seq in any pairwise comparisons were low, while the cpSSR genetic differentiation values varied with pairwise comparisons of populations. High gene flow and low genetic differentiation resulted in a weak isolation-by-distance effect. The genetic diversity and differentiation of T. sutchuenensis explained its survival in the Daba mountain chain, while its narrow ecological niche from relatively isolated and unique environment in the “refugia” limited its distribution.